2018
DOI: 10.1103/physrevphyseducres.14.010137
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional item response theory and the Force Concept Inventory

Abstract: Research on the test structure of the Force Concept Inventory (FCI) has largely been performed with exploratory methods such as factor analysis and cluster analysis. Multidimensional Item Response Theory (MIRT) provides an alternative to traditional exploratory factor analysis which allows statistical testing to identify the optimal number of factors. Application of MIRT to a sample of N ¼ 4716 FCI post-tests identified a 9-factor solution as optimal. Additional analysis showed that a substantial part of the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 66 publications
4
54
0
1
Order By: Relevance
“…The incorrect communities identified were generally consistent with those identified by MMA. The correct communities generally followed those identified by Stewart et al [16]; therefore, MMA-P productively identified both correct solution structure and incorrect structure at the same time. MMA-P also identified communities which mixed correct and incorrect answers.…”
Section: Discussionsupporting
confidence: 60%
“…The incorrect communities identified were generally consistent with those identified by MMA. The correct communities generally followed those identified by Stewart et al [16]; therefore, MMA-P productively identified both correct solution structure and incorrect structure at the same time. MMA-P also identified communities which mixed correct and incorrect answers.…”
Section: Discussionsupporting
confidence: 60%
“…The optimal model presented in Study 2 and a similar study of the FCI [12] provide further evidence for the difference in coverage of the two instruments with the optimal model of the FCI requiring 19 principles (fundamental reasoning steps) while the optimal model of the FMCE required only 8 principles. The two instruments also differed starkly in their re-use of principles with the FCI rarely repeating the same set of principles on multiple items and the FMCE often repeating the same principles.…”
Section: The Fci and The Fmcementioning
confidence: 67%
“…"Cart on a Ramp" items (items 8-10) ask students to select the force on a cart as it moves up and down an incline. "Coin Toss -Force" items (items [11][12][13] ask students to select the force on a coin tossed in the air. "Force Graph" items (items [14][15][16][17][18][19][20][21] ask students about the force on a toy car as it moves across a low-friction surface; students select from a number of graphs.…”
Section: A the Fmce Instrumentmentioning
confidence: 99%
See 2 more Smart Citations